HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MENGEDAN IBU BERSALIN DENGAN KEJADIAN RUPTUR PERINEUM DI KLINIK PRATAMA CITRA MARINDAL - Hutabarat, Vitrilina -; Sitepu, Stefani Anastasi; Leni, Erlina (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
Perineal rupture is a condition in which the peritoneum tears during vaginal delivery and is causedesd bys a numbers of factors, including maternal, fetal and supportive factors. Factors influencing maternal peritoneal rupture include age, parity, rapid delivery, excessive pushing, fragility and swelling of the peritoneal membrane, pelvic anatomy, vaginal flexibility, presence of varicose veins and previous surgical procedures. Factors affecting the fetus such as macrosomia, abnormal appearance and congenital anomalies of the fetus. The aims of thiss study is to finds outs of this factors make affect the incidence of diaphragmatic rupture in women giving birth at Pratama Citra Marindal Clinic. The studies used a crosssectionalss designs withh a samples size of 30 respondents using chi-square statistical analysis. The results showed significant associations between maternal age, knowledge, attitude towards pushing during labor and peritoneal tears with a p-value of <0.05. Specifically, the study found a significant association between maternal age (p=0.007), knowledge (p=0.007), and attitude towards pushing (p=0.001) and peritoneal tears. Taken togetherr, thes findings highlights the importancess of maternal ages, familiarity withs childbirth, and pushing during labor as major factors influencing the likelihood of diaphragmatic rupture during labor.